Do Losses Trigger Deliberative Reasoning? - Jeffrey P. Carpenter; David Munro (Institute of Labor Economics (IZA), 2022)
There is a large literature evaluating the dual process model of cognition, including the biases and heuristic it implies. To advance this literature, we focus on what triggers decision makers to switch from the intuitive process (aka System 1) to the more deliberative process (aka System 2). Based on previous studies indicating that potential losses increase cognitive effort, we posit that losses may also differentially trigger System 2 reasoning. To evaluate this hypothesis, we design an experiment based on a task that has been developed to distinguish between System 1 and System 2 thinking – the cognitive reflection task. Replicating previous research, we find that losses elicit more effort (measured by the time spent on the task and the incidence of correct answers). However, we also find that losses differentially reduce the incidence of intuitive answers, consistent with triggering System 2. To complement these results, we provide tests of the robustness of our results using aggregated data, subgroup analysis and the imposition of a cognitive load to hinder the activation of System 2.
Keywords: C9; D9; 330; dual process theory; cognitive effort; loss; experiment